2020
DOI: 10.9734/jpri/2020/v32i1430609
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activities of Crude Extract of Lasiodiplodia pseudotheobromae IBRL OS-64 against Foodborne Bacterium, Yersinia enterocolitica

Abstract: The antibacterial and antibiofilm activities of crude extract of Lasiodiplodia pseudotheobromae IBRL OS-64 was studied and tested against a foodborne pathogenic bacterium, Yersinia enterocolitica. The ethyl acetate extract exhibited favorable antibacterial activity with the zone of inhibition was 20.3±0.6 mm compared to dichloromethane (15.0±0.3 mm) and butanol (9.0±0.3 mm) extracts. Minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) values of the extract were 125 and 250 µg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This could be due to the ability of plant extracts to curtail binding forces that promote cell attachments as suggested by [ 43 ]. According to a report by Taufiq and Darah [ 44 ], the negative value suggests that the bacteria reacted to the change in the environment, consequently producing a large amount of biofilm to annul the effect of the perceived unfavourable environmental condition. In addition, it is also suggested that the difficulty in total eradication of biofilm is because the consortium of microbial growth is formed by the interaction of multiple species.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the ability of plant extracts to curtail binding forces that promote cell attachments as suggested by [ 43 ]. According to a report by Taufiq and Darah [ 44 ], the negative value suggests that the bacteria reacted to the change in the environment, consequently producing a large amount of biofilm to annul the effect of the perceived unfavourable environmental condition. In addition, it is also suggested that the difficulty in total eradication of biofilm is because the consortium of microbial growth is formed by the interaction of multiple species.…”
Section: Discussionmentioning
confidence: 99%